STATUS GIZI TERHADAP USIA MENARCHE REMAJA PUTRI - Cia Aprilianti; Madyana Gina Mutiara (MEDIA ILMU KESEHATAN, 2020)
Background: Nutritional status is an important factor for assessing someone in good health or not suffering from diseases due to nutritional disorders. Abnormal nutritional status disrupts reproductive function. In this case, nutritional status is associated with the age of menarche. It is known that early age menarche has a risk of breast cancer. Objective: To determine the relationship between nutritional status and age of menarche. Method: Using a cross-sectional design. The sample size of 50 respondents, was selected using simple random sampling. Data collection includes assessing nutritional status, employment, and education of parents, both fathers and mothers, and physical activity using the PAQ-C questionnaire. Analysis of the data used in this study is the Chi-Square test and logistic regression test. Results: The results of the bivariate analysis showed a significant relationship between father's education and physical activity on the age of menarche with a p-value <0.05 and the results of the multiple logistic regression test showed there was a relationship between overweight status and physical activity on the age of menarche with a p-value < 0.05. Conclusion: Overweight nutritional status and mild physical activity show a significant relationship to the age of early menarche.